Respon Pertumbuhan Dua Kultivar Anggrek Bulan (Phalaenopsis Amabilis) Dengan Aplikasi Beberapa Jenis Penginduksi Pembungaan - Ningsih, Riani; Edi Nugroho, Suseno; Hadi Cahyono, Eko; Hasanah, Marmiatul; Hendaryono, Joko (Politeknik Negeri Jember, 2025)
Moon orchids are included in the group of ornamental plants which are epiphytes, that is, they attach to other plants without harming their hosts (Apriansi et al. 2021). However, many people think that caring for this type of orchid is complicated, especially caring for it until the plant flowers. PLP at the Jember State Polytechnic Tissue Culture Laboratory is in the development stage of moon orchid breeding both in vitro and in vivo. So far, adult orchids that are ready to flower have been treated because they do not meet the growth and development needs of moon orchids, so they do not appear flowers quickly or on time, which results in less than optimal development. The aim of this research is to obtain recommendations for the fastest and best type of flowering inducer in optimizing the growth of two cultivars of the moon orchid (phalaenopsis amabilis). This research method is testing and comparing several types of flowering inducers in moon orchids (Phalaenopsis amabilis) for seed production so that they can be used as a reference for inducing flowering in the development of orchid TEFA at the Jember State Polytechnic Tissue Culture Laboratory. The parameters observed in this research were the increase in plant height, increase in the number of leaves, increase in leaf width, increase in leaf length, leaf chlorophyll content, time for the first spike to appear and time for the first flower to appear.